KOMPETENSI, INDEPENDENSI, DAN MOTIVASI SEBAGAI DETERMINAN KINERJA AUDITOR INTERNAL PEMERINTAH - Agustina, Lisa; Sulardi, Sulardi (Universitas Muhammadiyah Malang)
This research proposes to test and find empirical evidence about the influence of competence, independence, and the motivation of internal government auditor performance. These samples are internal auditor with Functional Auditor (JFA) position and Control Officers (P2UPD) in Inspectorate Klaten Regency. This research used quantitative approach to entire population which is 40 internal auditors. Sampling technique on this research using census with multiple regression analysis method. The result of this research proves that the competence influence both positive and significant to auditors’ performance, independence influence both positive and significant to auditors’ performance, and motivation influence both positive and significant to auditors’ performance. Therefore, local government should provide training in case for increasing competence, encourage auditor’s performance by increasing independence, and strengthen motivation so that the internal auditor can take the role and the function as well as possible so the achievement of local government objectives can be implemented accountably.Keywords: competence, independence, motivation, auditors’ performance